Induction of lung-like cells from mouse embryonic stem cells by decellularized lung matrix - Kawai, Norikazu (Biochem Biophys Rep, 2018)
Decellularization of tissues is a recently developed technique mostly used to provide a 3-dimensional matrix structure of the original organ, including decellularized lung tissues for lung transplantation. Based on the results of the present study, we propose new utilization of decellularized tissues as inducers of stem cell differentiation. Decellularized lung matrix (L-Mat) samples were prepared from mouse lungs by SDS treatment, then the effects of L-Mat on differentiation of ES cells into lung cells were investigated. ES cell derived-embryoid bodies (EBs) were transplanted into L-Mat samples and cultured for 2 weeks. At the end of the culture, expressions of lung cell-related markers, such as TTF-1 and SP-C (alveolar type II cells), AQP5 (alveolar type I cells), and CC10 (club cells), were detected in EB outgrowths in L-Mat, while those were not found in EB outgrowths attached to the dish. Our results demonstrated that L-Mat has an ability to induce differentiation of ES cells into lung-like cells.